Barriers and Facilitators to the Implementation of the Pathways to Comorbidity Care (PCC) Training Package for the Management of Comorbid Mental Disorders in Drug and Alcohol Settings - Louie, Eva; Giannopoulos, Vicki; Baillie, Andrew; Uribe, Gabriela; Wood, Katie; Teesson, Maree; Childs, Steven; Rogers, David; Haber, Paul S.; Morley, Kirsten C. (Frontiers in Health Services, 2021)
Background: We have previously reported that the Pathways to Comorbidity Care (PCC) training program for alcohol and other drug (AOD) clinicians improved identification of comorbidity, self-efficacy, and attitudes toward screening and monitoring of comorbidity. We aimed to identify barriers and facilitators of implementation of the PCC training program in drug and alcohol settings. Methods: The PCC training program was implemented across 6 matched sites in Australia as per (1), and 20 clinicians received training. PCC training included seminar presentations, workshops conducted by local “clinical champions,” individual clinical supervision, and access to an online information portal. We examined barriers and facilitators of implementation according to the Consolidated Framework for Implementation Research. Results: Barriers included inner setting (e.g., allocated time for learning) and characteristics of individuals (e.g., resistance). Facilitators included intervention characteristics (e.g., credible sources), inner setting (e.g., leadership), and outer setting domains (e.g., patient needs). Clinical champions were identified as an important component of the implementation process. Conclusions: Barriers included limited specific allocated time for learning. A credible clinical supervisor, strong leadership engagement and an active clinical champion were found to be facilitators of the PCC training program.